Strategy and business process management : techniques for improving execution, adaptability, and consistency - Lehmann, Carl F. (Boca Raton, FL : CRC Press, 2012)
'This book prepares readers to master an IT and managerial discipline quickly gaining momentum in organizations of all sizes--Business Process Management (BPM). It describes how BPM treats processes as a portfolio of strategic assets that create and deliver customer and shareholder value and adapt, when necessary, enabling competitive advantage through consistent performance. Strategy and Business Process Management: Techniques for Improving Execution, Adaptability, and Consistency defines the planning framework and managerial mindset necessary to craft and drive highly effective business process improvement projects and continuous improvement programs. Readers will learn specific techniques used by industry leaders to formulate and execute business strategy that adapts organizational behavior, business processes and information technology as a dynamic system designed to assure consistent performance and achievement, even when challenged with unexpected change or opportunity'--
'Preface ABOUT THIS BOOK Running a business often requires leaders and management teams to do things better and faster with fewer resources and at lower cost. Some organizations always seem to adapt and flourish at this and others struggle. Why? Those that succeed do so because they always look at how they do things and continuously ask,'How can we run our business better?' They answer the question by first learning the best practices of other highly successful organizations. Next, they look inward, studying how they currently do things. They then take what they've learned and experiment with changes, testing new ways to work smarter, better, and faster at lower cost using the resources at hand. But doing this requires research, knowledge, planning, and tools. Proficiency and skills must be garnered from several disciplines that include the following - Crafting and adapting a competitive and defensible business strategy - Translating business strategy into action - Empowering and motivating the workforce - Designing effective and efficient business processes - Implementing information technology for cost-effective execution - Aligning resources such as people, processes, and technology to consistently execute business strategy Execution requires mastery of several skills including the following: - Insightful leadership capable of orchestrating a multidisciplinary management team'--
Includes bibliographical references and index.
Keywords: Strategic planning; Management; Business logistics